PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERORIENTASI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) PADA MATERI TURUNAN UNTUK SISWA KELAS IX IPA PROGRAM AKSELERASI - Sumanah Sumanah; Mardiyana Mardiyana; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this study were: (1) to develop a valid mathematics learning set which is oriented to Creative Problem Solving (CPS) learning model in the topic of derivative on XI Acceleration grade, and (2) to determine which learning model produces better learning achievement, the developing CPS or the conventional model in the topic of derivative on XI Acceleration grade. The development of learning set in this study were observed from five aspects, they are: (1) the expert's validity, (2) the students' activity, (3) the teacher's capability in managing teaching and learning process, (4) the students' response to the learning process, and (5) the students' mathematics learning achievement. This study was a development study of learning set done by applying a modified 4-D Thiagarajan model. There were three phases involved in this study; i.e. defining, designing, and developing. The subjects of the study were the students of SMA N 1 Pati grade XI acceleration year 2013/2014 as the experiment class and the students of SMA 1 Kudus grade XI acceleration year 2013/2014 as the control class. The data was collected by using validation sheet of learning set, observation sheet of teacher's capability in managing teaching and learning process, observation sheet of students' activity, students'response questionnaire, and test of students' learning achievement. Data analysis was done by descriptive and inferential statistics. The learning set produced is valid, because it has been validated with high score, that is 4.41 and after finishing the experiment, the results fulfill the pre-requirements, defined as follows: it leads to productive students' activity with average score of 4,25 having a positive effect, teacher's capability in managing teaching and learning process is very good with the score above 4,20, students' response toward the teaching and learning process is positive with the precentage above 80%, and learning achievement test is proven to be valid, reliable. Moreover, the teaching and learning process with CPS model with developing learning set is effective, because the experiment showed that the average score of learning achievement of the student is better than the conventional model.Keywords : Creative Problem Solving (CPS), The learning set